Síntesis y caracterización de materiales nanoestructurados de Ni y Mo depositados sobre bentonita - Escobar, Beatriz; lbarra, Sara; Reyes, Adriana; Verde, Ysmael; Barbosa, Romeli; Valenzuela, Ana; Melo , José (Universidad Autónoma de Nuevo León, 2014)
Recently, clay has been accepted as excellent adsorbents, catalyst, fillers in industry. The wide usefulness of bentonite is essentially as a result of its high specific surface area, high chemical and mechanical stabilities, and a variety of surface and structural properties. Nickel and molybdenum nanoparticles with particle size distribution ranging between 30-50 nm were synthesized by chemical reduction of ions using nickel nitrate hexahydrate (Ni(NO3)6.6H2O) and ammonium molybdate tetrahydrate (NH4)6Mo7O24.4H2O) in methanol solution, respectively. The process for reducing Pt nanoparticles was carried out in presence of NaBH4, Poly(N-vinylpyrrolidone) was used as protecting agent of the obtained particles. The synthesis process was performed at room temperature. The colloidal dispersions of Ni and M were supported on bentonite by impregnation method, and then were dried at around l00ºC until the solution was completely evaporated. The anchoring of Ni and Mo nanoparticles on the bentonite surface was carried out by a thermal process in a tubular furnace adapted with a quartz tube, where samples were annealed at 400ºC under nitrogen atmosphere for 30 min with a flow rate of 50 ml min-1. The obtained samples were chacterized using X-ray diffractometer (XRD), scanning electron microscope (SEM) and X-ray energy dispersive spectrormeter (EDS). In X-rays analysis for Ni sample was possible to observe peaks of metallic Ni and formation of NiO2, where as for molybdenum appeared diffraction peaks corresponding to the phases of Mo and MoO3. Through SEM waS possible to observe the morphology of the sample and Incorporation of the metal nanoparticles of Ni and Mo, Impregnated on the support. The characterization also reveals the well disperse of these obtained Ni and Mo nanoparticles supported on the external surface of clay with roughly spherical morphology and mean diameter of 30 nm. Finally, using the EDS technique was possible to estimate the actual load on bentonite catalysts.